Sugiol, a diterpenoid: Therapeutic actions and molecular pathways involved. (January 2021) - Bajpai, Vivek K.; Sonwal, Sonam; Hwang, Seung-Kyu; Shukla, Shruti; Khan, Imran; Dey, Debasish Kumar; Chen, Lei; Simal-Gandara, Jesus; Xiao, Jianbo; Huh, Yun Suk; Han, Young-Kyu
Graphical abstract: Highlights: Sugiol exhibits antioxidant potential. Sugiol demonstrates antimicrobial potential. Sugiol displays antiviral activity. Sugiol represents anti-inflammatory potential. Sugiol possesses anti-cancer activity. Abstract: Understanding how the natural products structural diversity interacts with cellular metabolism and infectious disease targets remains a challenge. Inflammation is an important process in the human healing response in which the tissues respond to injuries induced by many agents, including pathogens. In recent years, several drugs derived from plant products have been developed, and current drug research is actively investigating the pharmacotherapeutic role of natural products in advanced multimodal inflammatory disease targeting. Sugiol, a diterpenoid, can act as an antimicrobial, antioxidant, anti-inflammatory, anti-carcinoma, antiviral, and cardiovascular agent. Until now, there have been no updates on the pharmacotherapeutic advancement of sugiol. Herein, we correlate the diverse molecular pathways in disease prevention involving sugiol. We also discuss the origins of its structural diversity and summarize new research directions toward exploring its novel effective future uses. Despite much evidence of its efficacy and safety, the sugiol has not yet been approved as a therapeutic agent due to its low bioavailability, and insolubility in an aqueous environment. The aim of this review is to renew and update noteworthy information on the pharmacotherapeutic characteristics of sugiol to approach different advanced strategies employed in the context of natural nurturing-based biomedicine.